A solution for SRM starting hesitation: from FE analysis to bench validation. Issue 6 (2nd November 2015) - Makni, Zaatar; Bouallaga, Kamel
Abstract : Purpose: – The starting hesitation of a switched reluctance motor (SRM) is an issue which must be considered in the early motor design. It is mostly handled as a control concern. The starting procedure of a SRM using a single Hall-effect position sensor is analysed in this paper. This low cost position measurement solution requires a specific control strategy. That has been developed for a three-phase 6/4 SRM. The paper aims to discuss these issues. Design/methodology/approach: – The starting procedure begins with a rotor alignment step intending to bring the rotor to a known position. Afterward, only one phase is supplied on a periodic basis, to drive the rotor in the desired direction and accelerate up to a predefined speed threshold. Thus, the proposed procedure drastically simplifies the control strategy and permits a low cost sensor based control. 2D finite elements simulations are performed to analyse the starting performances in terms of response time and power efficiency. Both electrical and mechanical transients are considered in the simulation model thanks to simplifying assumption which consists in applying a time averaged voltages instead of instantaneous switching. Finally, the entire starting procedure with a one phase supply procedure is tested experimentally. Findings: – A starting procedure of a three-phase SRM is implemented. The control effectiveness is validated by complementary FE calculations and measurements. Originality/value: – The starting hesitation issue of a three-phase SRM is solved with an easy control strategy. During the acceleration phase, only one phase is self-controlled.